Smartphone and Internet Addictive Behaviors Are Differentially Associated with Mediterranean Diet Adherence in Young Adults: The EVA-Adic Study. - Vicente-Prieto, Alberto; Lugones-Sánchez, Cristina; Vicente-Gabriel, Sara; Saldaña-Ruiz, Cristina; González-Sánchez, Susana; Conde-Martín, Sandra; Gómez-Marcos, Manuel A.; Gómez-Sánchez, Marta; Gómez-Sánchez, Leticia (Nutrients, 2026)
Background/Objectives: Problematic digital technology use may be associated with unhealthy dietary behaviors, but different forms of digital dependence may not relate to diet quality in the same way. This study examined the association between Mediterranean diet adherence and problematic smartphone, Internet, and video game use in young adults. Methods: A cross-sectional study was conducted in 496 adults aged 18–34 years participating in the EVA-Adic study. Mediterranean diet adherence was assessed using the 14-item Mediterranean Diet Adherence Screener (MEDAS). Problematic digital use was evaluated using the EDAS-18 for smartphone dependence, the Compulsive Internet Use Scale (CIUS), and the Questionnaire of Experiences Related to Video Games (CERV). Multivariable regression models were adjusted for sociodemographic, anthropometric, and lifestyle factors. Results: Of the participants, 339 had low-to-moderate Mediterranean diet adherence, and 157 had high adherence. In fully adjusted models, higher EDAS-18 scores were associated with lower MEDAS scores (β = −0.022; 95% CI: −0.041 to −0.003), whereas higher CIUS scores showed a small positive association with MEDAS scores (β = 0.025; 95% CI: 0.002 to 0.049). CERV scores and the global digital addiction index were not associated with overall Mediterranean diet adherence. At the individual dietary-component level, higher smartphone dependence was associated with lower compliance with fruit and sugar-sweetened beverage recommendations. Conclusions: In this cross-sectional sample of young adults, smartphone dependence and compulsive Internet use showed small associations with Mediterranean diet adherence in opposite directions, whereas problematic video-game use and the exploratory global composite were not associated with the overall MEDAS-14 score. The magnitude of the observed associations was modest; their clinical and public-health relevance remains uncertain, and the component-level findings should be considered exploratory in the context of multiple testing. These results do not establish causality and require confirmation in longitudinal, multicenter studies using objective and context-specific measures of digital use.